Malala's Worldview in The Autobiography I Am Malala by Malala Yousafzai: Study of Genetic Structuralism - Fikri, Maulana Muhammad; Jambak, Melinda Raswari; Aprilia, Lulu Eka (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
ملالا يوسفزاي هي فتاة مراهقة ترغب في النضال من أجل حقوق تعليم النساء. تتضمن هذه الدراسة هدفين، الأول هو الكشف عن أربعة أمور: الحقائق الإنسانية، الموضوع الجماعي، بنية الأعمال الأدبية، ورؤية الكاتب. الهدف الثاني هو التركيز على رؤية العالم للكاتب. تعتبر هذه البحث نوعًا وصفيًا ذا طابع نوعي، مع تقنيات جمع البيانات، وهي تقنيات دراسة الأدب. تقنية تحليل البيانات هي الأسلوب الجدلي: الفهم - التفسير. هناك نتيجتان ناتجتان عن هذا البحث. الأولى، نتائج تتعلق بأربعة جوانب من الهيكل الوراثي للجينات لوسيان جولدمان. الثانية، رؤية ملالا، متجذرة بعمق في السياقات الجغرافية والاجتماعية والتاريخية، تحفز على التغيير. تلقي هذه التحليل الشامل الضوء على الجوانب متعددة الأبعاد للسرد الخاص بملالا ودورها المحوري في الترويج لحقوق التعليم وحقوق النساء.   Malala Yousafzai is a teenage girl who wants to fight for women's education rights. This study has 2 goals, first is to reveal 4 things: humanitarian facts, collective subject, the structure of literary works, and the author's worldview. Second, is to focus on the author’s worldview. This research is a descriptive qualitative type, with data collection techniques, namely literature study techniques. The data analysis technique is the dialectical method: understanding-explanation. There are two findings as a result of this research. First, results regarding 4 parts of Lucien Goldmann’s genetic structuralism. Second, Malala's worldview, deeply rooted in geographical, sociological, and historical contexts, catalyzes change. This comprehensive analysis sheds light on the multi-dimensional aspects of Malala's narrative and her pivotal role in advocating for education and women's rights.